RANCANG BANGUN MODEL SISTEM INFORMASI PELAYANAN TERPADU SATU PINTU UNTUK MENINGKATKAN KUALITAS PELAYANAN SEKOLAH - Al Husain; Ayu Nur Athiyyah Effendi; Meisah Nurma Novita (UNIVERSITAS RAHARJA, 2020)
The service process in some schools is still running ineffectively, due to the aging process, such as the use of ledgers for archiving and recording of data that is managed, this requires a long time and a large cost, so it is deemed ineffective and inefficient. To overcome this problem, a computerized system is needed so that it can overcome the problem and be able to assist in speeding up the process, besides that it can improve the quality of service. This study proposes the design of a one-stop integrated service information system automatically using various methods including methods of data collection through the process of observation and interviews, current and expected analysis methods using pieces to evaluate performance and design methods using uml (unified modeling language) which includes usecase diagrams, squares diagrams and activity diagrams as tools to describe object-oriented programming languages and the use of mysql for database management, which in turn will produce a wellintegrated system. So this research can improve the quality of school services.